Effect of L‐theanine on sensorimotor gating in healthy human subjects. Issue 5 (25th December 2013) - Ota, Miho; Wakabayashi, Chisato; Matsuo, Junko; Kinoshita, Yukiko; Hori, Hiroaki; Hattori, Kotaro; Sasayama, Daimei; Teraishi, Toshiya; Obu, Satoko; Ozawa, Hayato; Kunugi, Hiroshi
<x xml:space="preserve">Abstract</x> Aim l‐Theanine (N‐ethyl‐l‐glutamine) is an amino acid uniquely found in green tea. Growing evidence has suggested the possible effects of l‐theanine on cognition. Previously, we found that l‐theanine attenuates MK‐801‐induced deficit in prepulse inhibition (PPI) in mice. In this study, we examined the effect of l‐theanine in increasing the PPI in healthy humans. Methods The subjects were 14 healthy adults who underwent PPI testing as a measure of sensorimotor gating 90 min after an oral intake of l‐theanine (0, 200, 400, or 600 mg). PPI tests were done by examiners who were blind to the dose. Results The administration of 200 mg of l‐theanine and that of 400 mg, but not 600 mg, significantly increased the % PPI compared to the baseline (0 mg). There was no significant relation between the dose of l‐theanine and the startle magnitude or the habituation of startle response. The plasma concentrations of l‐theanine correlated with the dose of l‐theanine. Conclusion The observed effect with 200–400 mg of l‐theanine on PPI suggested that l‐theanine at a particular dose range increases sensorimotor gating in humans.